2010
DOI: 10.1136/emj.2009.079558
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitudes of Chinese students towards cardiopulmonary resuscitation

Abstract: Dissemination of CPR among Chinese students has not been executed satisfactorily. The finding highlights the importance of CPR dissemination and efforts should be made to provide more convenient, effective and attractive ways for the Chinese public, especially students, to learn CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
(14 reference statements)
2
15
1
Order By: Relevance
“…If the students share the acquired knowledge with their family and non-trained friends, it indirectly introduces the BLS training to a broader audience, as previously shown [8]. Finally, the positive attitude towards learning BLS among high school students [14] could be a critical determinant of the impact of these short training sessions and emphasizes the importance to cease this golden opportunity to increase the knowledge on BLS at an early time in life.…”
Section: Discussionmentioning
confidence: 95%
“…If the students share the acquired knowledge with their family and non-trained friends, it indirectly introduces the BLS training to a broader audience, as previously shown [8]. Finally, the positive attitude towards learning BLS among high school students [14] could be a critical determinant of the impact of these short training sessions and emphasizes the importance to cease this golden opportunity to increase the knowledge on BLS at an early time in life.…”
Section: Discussionmentioning
confidence: 95%
“…This study showed that the number of people who understood what is CPR was greatly extended than 7 years ago (90% versus 55%) [16]. However, layperson CPR training (25.6%) in China is still lower than most developed countries, such as Sweden (54.4%) [22], Slovenia (69.4%) [11], United States (54.1%) [23, 24], Australia (58%) [25], and New Zealand (76%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Seventy percent of people in Japan learned CPR, and 30% of people learned CPR more than two times [10]. However, CPR training among Chinese students is 27%, which was much lower than in developed countries [10, 12, 15, 16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4(12), 335-338 336 through utilizing device. It aims to preserve brain function which can be lifesavingand may increase the rate of survival two to three times comparing to those who didn't receive CPR [1][2][3][4][5].…”
Section: Introduction:-mentioning
confidence: 99%